The Role of The Educational Program in The Implementation of The Credit-Module System of Education in Higher Education Institutions of Our Country - O’sarov Dilshodjon G’ulom o’g’li; Mamarasulov Sobirjon Odiljon o’g’li (Euro Asian Journal Publishing, 2024)
This article talks about the credit-module system of higher education in our country, its introduction, as well as the organization of the educational program structure in this educational system. This article can be used by representatives of the relevant field as theoretical and methodological information.
Keywords: Credit Module System Of Education; Implementation In Higher Education Institutions; Structure Of The Educational Program